2007
DOI: 10.1002/cne.21338
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical characterization of substance P receptor (NK1R)‐expressing interneurons in the entorhinal cortex

Abstract: It has been reported that application of substance P (SP) to the medial portion of the entorhinal cortex (EC) induces a powerful antiepileptic effect (Maubach et al. [1998] Neuroscience 83:1047-1062). This effect is presumably mediated via inhibitory interneurons expressing the neurokinin-1 receptor (NK(1)R), but the existence of NK(1)R-expressing inhibitory interneurons in the EC has not yet been reported. The present immunohistochemical study was performed in the rat to examine the existence and distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 86 publications
(105 reference statements)
2
14
0
Order By: Relevance
“…It produced a pattern of labeling in the rat hippocampus, entorhinal cortex, and hypothalamus that was consistent with previous studies (Markakis et al, 2004;Wolansky et al, 2007). Both types of anti-SOM antibodies used here produced identical patterns of labeling of subpopulations of interneurons in the aPC (see Results), similar to the staining patterns reported for somatostatin in the rat PC (Cummings, 1997;Ekstrand et al, 2001a).…”
Section: Anti-somatostatinsupporting
confidence: 89%
“…It produced a pattern of labeling in the rat hippocampus, entorhinal cortex, and hypothalamus that was consistent with previous studies (Markakis et al, 2004;Wolansky et al, 2007). Both types of anti-SOM antibodies used here produced identical patterns of labeling of subpopulations of interneurons in the aPC (see Results), similar to the staining patterns reported for somatostatin in the rat PC (Cummings, 1997;Ekstrand et al, 2001a).…”
Section: Anti-somatostatinsupporting
confidence: 89%
“…Despite the direct effects of SP on NK1 neurons described here, there is a spatial mismatch between the NK1 receptor and SPergic axon terminals in the cortex (Liu et al, 1994; Vruwink et al, 2001; Wolansky et al, 2007). Cortical SPergic neurons are GABAergic and about 70% of this population co-express Parvalbumin in the rat (Kaneko et al, 1998; Vruwink et al, 2001).…”
Section: Discussionmentioning
confidence: 79%
“…Therefore, it was suggested that SPergic neurons release SP as a volume transmitter and are, in turn, modulated by NO released from the NK1/nNOS neurons, forming a non-synaptic cortical feedback loop (Vruwink et al, 2001). However, SPergic afferents to the cortex have also been found to originate from the laterodorsal tegmental nucleus (Vincent et al, 1983) and it cannot be excluded that other subcortical sources exist (see Wolansky et al, 2007). Furthermore, NK1 is the preferred receptor not only for SP, but also for the more recently discovered tachykinins hemokinin-1 and endokinin A and B (Page, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies against SP were used to identify the direct pathway MSN collaterals, whereas the indirect pathway MSN collaterals were identified with polyclonal antibodies against Met‐Enk and Leu‐Enk (Table 1). The specificity of the SP antibodies used in this study have been demonstrated by showing the equal displacement of labeled SP by five‐, six‐, and eight‐amino acid COOH‐terminal fragments of SP, as well as full‐length SP, and by the specific binding of these antibodies with cell bodies and terminals located in well‐defined SP‐containing nuclei in the central nervous system (Cuello et al,1979; Beach and McGeer,1984; Bolam and Izzo,1988; Smith et al,1998; Reiner et al,1999, Wolansky et al,2007). The lack of tissue labeling following incubation with nonimmune rat serum or primary antibodies preabsorbed with SP further confirmed the specificity of these antibodies (Cuello et al,1979; Mai et al,1986).…”
Section: Methodsmentioning
confidence: 99%